The path to open-source systems. - Comerford, R.
A new model for software development and distribution, called open-source, promises to breath new life into Unix software and increase competition in operating systems. Arising from the historical openness of the academic and engineering environment, it is starting to attract commercial interest as well
Keywords: Unix software; Commercial interest; Competition; Open-source systems; Operating systems; Software development; Software distribution